HUBUNGAN DAYA LEDAK OTOT LENGAN DAN BAHU DENGAN KETEPATAN SMASH PADA PB. PANGKALAN BUNUT - Herry Afrinaldi; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Based on the observation that in doing research in the field, the ability to smash the Club PB accuracy. Bunut base is still low. This is presumably low explosive power arm and shoulder muscles. The aim in this study was to examine the relationship explosive power arm and shoulder muscles with precision smash on PB. Bunut base. The population in this study is the player PB, amounting to 17 people. Sampling techniques in using total sampling technique, in which the entire population be made in the sample. Data obtained from measurements of medicine put two hand ball and smash ability. Data were analyzed by using correlation produc moment. Based on the results of the analysis and discussion and is described in the previous section, then in this chapter can be concluded and the advice Explosive power arm and shoulder muscles associated with the precision of a smash in badminton PB Base Bunut. The analysis showed that rhitung> rtabel at α = 0.05.Keywords: Explosive Power Arm and Shoulder Muscles, Smash